Nalar-Moderat Mazhab Mutakallimin dan Implikasinya pada Pencatatan Nikah di Indonesia - Mansur Mansur; Abu Yasid; Lathoif Ghozali; Iskandar Ritonga (ASASI: Journal of Islamic Family Law, 2023)
The purpose of this study is to explain moderate thoughts in the deductive reasoning of the Mutakallimin School and their implications for influencing state policy in Indonesia, especially in the matter of registering marriages. With the regulation of Law no. 1 of 1974 concerning the obligation to register marriages through the KUA, reaping controversy and recent deviant behavior such as online siri marriages. This manuscript study using the Content Analysis method examines the deductive method of the Mutakallimin School included in the book Al-mahshul fi ilmi al ushul. As a result, the moderate reasoning of the Mutakalllimin School with the pioneers of the two Ar-Razi, namely Rhazes (925 AD) and Ar-Razi through linguistic studies of deductive reasoning has a moderate character, so that it has implications for the regulation of marriage registration at the Office of Religious Affairs (KUA) extracted from the pronunciation of ' am mutlaq "tadaayantum" in the Al-Qur'an Surah Al-Baqarah: 282.